Pelatihan Aplikasi Bahasa Inggris dalam Pembelajaran bagi Guru di SMK Al Hasra Sebagai Upaya Mewujudkan Sekolah Go Internasional - Hariyanti, Yuni; Purwandari, Junita Duwi; Kuswanti, Ana (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to improve English skills and learning for SMK Al Hasra teachers to make the school go international. The method of implementing this service used training which included the preparation, socialization, implementation, and evaluation stages. The instrument for evaluating this activity used a questionnaire and was analyzed descriptively. This service showed an increase in the teacher's ability to master English language applications, namely English as a Medium of Instruction and General English material, including listening, speaking, reading, and writing. In addition, there was a positive response and satisfaction from the school for the training that had been provided.